2010
DOI: 10.2478/v10007-010-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of some synthesized glucopyranosyl-pyrimidine carbonitrile and fused pyrimidine systems

Abstract: Antimicrobial activity of some synthesized glucopyranosyl-pyrimidine carbonitrile and fused pyrimidine systems 3-Amino-5-(4-chlorophenylamino)-4-cyanofuran-2-carboxamide (2) was used as the key molecule for preparation of various furopyrimidines 3-9 and formation of spiro-cycloalkane furopyrimidines 10, 11. Also, poly fused heterocyclic compounds 13-17 were prepared from compound 2. The synthesized compounds were screened for their antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The compound of the present study, 2-Medpy-3-CN, harbors nitrile as a functional group, which is another likely perception for its strong antimicrobial properties. Carbonitrile-containing semisynthetic derivatives of pyridine molecules exhibit strong antibacterial activity [32,33,34]. In addition to antibacterial activity, 2-Medpy-3-CN also exhibited very strong anticandidal activity, attributed to a broad-spectrum antimicrobial activity at a very low MIC level of 2 µg·mL −1 for C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…The compound of the present study, 2-Medpy-3-CN, harbors nitrile as a functional group, which is another likely perception for its strong antimicrobial properties. Carbonitrile-containing semisynthetic derivatives of pyridine molecules exhibit strong antibacterial activity [32,33,34]. In addition to antibacterial activity, 2-Medpy-3-CN also exhibited very strong anticandidal activity, attributed to a broad-spectrum antimicrobial activity at a very low MIC level of 2 µg·mL −1 for C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reported that certain of our newly substituted heterocyclic compounds exhibited antiparkinsonian [21], antitumor [22][23][24], antimicrobial [25] and anti-inflammatory [26] activities. Recently, some new substituted heterocyclic derivatives have been synthesized [27], which exhibit antimicrobial [28,29], analgesic, antiinflammatory and activities [30][31][32][33][34][35]. In view of these observations and as continuation of our previous works in heterocyclic chemistry, we have herein synthesized some new poly heterocyclic fused ring systems containing pyrazole nuclei, and tested their antiinflammatory, analgesic and antimicrobial activities in comparison to indonethacin, valdoxib, tertacycline, ketoconazole, bleomycin, gallic acid as positive controls.…”
Section: Introductionmentioning
confidence: 91%
“…A common strategy for bfused heterocycles 371 has been condensation of a cyclic thiourea 370 with a 3-halopropionic acid 369, where the halide is bromine or chlorine [201][202][203][204][205] (Scheme 111). In one case, instead of NaOAc/Ac 2 O/AcOH/reflux (52%), ionic liquid N-methylpyridinium tosylate was used at 100-110 °C (68%).…”
Section: B-fused 2-imino or 2-amino Derivatives Of 56-dihydro-13-thiazin-4-onesmentioning
confidence: 99%